Light-responsive polymer brushes: active topographic cues for cell culture applications. Issue 21 (5th May 2017) - Kollarigowda, R. H.; Fedele, C.; Rianna, C.; Calabuig, A.; Manikas, A. C.; Pagliarulo, V.; Ferraro, P.; Cavalli, S.; Netti, P. A.
Abstract : Azopolymer brushes were patterned using interference lithography and erased using ultrasonication. This substrate was able to induce cell orientation. Abstract : In the call for novel stimuli-responsive biomaterials, azobenzene-containing polymer brushes entail a remarkable potential. In fact, their ability to be patterned at the micro- and nanoscale using interference lithography (IL) might be exploited for the realisation of cell-instructive materials (CIMs). In this work, Disperse Red 1 (DR1)-based photoresponsive polymer brushes were synthesised using a controlled radical polymerisation technique. A sinusoidal pattern was inscribed on the azopolymer brush samples using Lloyd's IL configuration. Interestingly, we found that seeded human umbilical vein endothelial cells (HUVECs) oriented in the pattern direction. Furthermore, using a non-cytotoxic ultrasonication treatment, pattern erasure was achieved. Hence, we envisage the possibility of using these surfaces as reconfigurable cell-instructive biomaterials for tissue engineering applications.